PENGELOLAAN PENDIDIKAN DALAM PERSPEKTIF FUNGSI MANAJEMEN (POACH) - Shafa, Fadiyah; April Aulia; Farha V. Lasahido; Nurhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research includes library research. The technique used in this research is to use lots of references related to the research theme in question, namely education management in the perspective of poac hmanagement functions. The entire series of learing aims to create conditions here students are active in learning and develop their understanding, improve the quality of learning and build effective and efficient learning and learning objectives or competencies can be achieved in accordance ith planned decisions. Management has tasks that must be carried out. This task can be called the management function, hich consists of planning, organizing, actuating, controlling. The entire series in management aims to create conditions to help improve the educational process a person is formed to become a quality individual. The results of this research sho that educational management from the management perspective of poac itself in education is to increase the effectiveness and efficiency of management in educational attainment.